Factors Contributing to In-Hospital Mortality in Dengue: Insights from National Surveillance Data in Mexico (2020–2024) - Eder Fernando Ríos-Bracamontes; Oliver Mendoza-Cano; Agustin Lugo-Radillo; Ana Daniela Ortega-Ramírez; Efrén Murillo-Zamora (Tropical Medicine and Infectious Disease)
This study aimed to identify the factors associated with all-cause in-hospital mortality in laboratory-confirmed dengue cases from 2020 to mid-2024. A nationwide retrospective cohort study was conducted in Mexico and data from 18,436 participants were analyzed. Risk ratios (RRs) and 95% confidence intervals (CIs), estimated using generalized linear regression models, were used to evaluate the factors associated with all-cause in-hospital mortality risk. The overall case–fatality rate was 17.5 per 1000. In the multiple model, compared to dengue virus (DENV) 1 infections, DENV-2 (RR = 1.81, 95% CI 1.15–2.86) and DENV-3 (RR = 1.87, 95% CI 1.19–2.92) were associated with increased mortality risk. Patient characteristics, such as increasing age (RR = 1.02, 95% CI 1.01–1.03), type 2 diabetes mellitus (RR = 2.07, 95% CI 1.45–2.96), and chronic kidney disease (RR = 3.35, 95% CI 2.03–5.51), were also associated with an increased risk of a fatal outcome. We documented the influence of both the virus and individual susceptibility on mortality risk, underscoring the need for a comprehensive public health strategy for dengue.